Public investment in the Berlin state budget: Education and transport are falling short - Arnold Felix; Johannes Brinkmann; Maximilian Brill; Ronny Freier (DIW Economic Bulletin, 2016)
In Berlin, as elsewhere, public investment is critical to an individual's life satisfaction and a prerequisite for positive economic development. There are many fields of activity for public investment. For instance, the tasks for Berlin include a sustainable transport concept that maintains and develops the local passenger transport network, a sustainable cycle concept, new schools need to be built and old ones need renovating, and Berlin must find answers to problems in its housing market. A glance at Berlin's public investment activities reveals a mixed picture. In 2014, the city invested a total of 2.8 billion euros in its core budget and in local public firms, equivalent to around 810 euros per inhabitant. This means the capital city is worse off than Hamburg, for example. To strengthen public investment activity, Berlin's administrative practices should be thoroughly reviewed in order to gain an overview of its asset situation and public investment requirements. In addition, it is recommended that the structure be organized in content-related special funds or public enterprises with their own personnel and extensive rights to assert claims-similar to Grün Berlin GmbH. Since schools are one of the most important locational factors, not only must gaps in the school infrastructure be closed but also more teachers need to be employed.
Keywords: H70; 330; Berlin state budget; public investment; local public firms